Role of emerging private hospitals in a post-Soviet mixed health system: a mixed methods comparative study of private and public hospital inpatient care in Mongolia. Issue 4 (22nd December 2016) - Tsevelvaanchig, Uranchimeg; Gouda, Hebe; Baker, Peter; Hill, Peter S
Abstract: Background The collapse of the Soviet Union in 1990 severely impacted the health sector in Mongolia. Limited public funding for the post-Soviet model public system and a rapid growth of poorly regulated private providers have been pressing issues for a government seeking to re-establish universal health coverage. However, the evidence available on the role of private providers that would inform sector management is very limited. This study analyses the current contribution of private hospitals in Mongolia for the improvement of accessibility of health care and efficiency. Methods We used mixed research methods. A descriptive analysis of nationally representative hospital admission records from 2013 was followed by semi-structured interviews that were carried out with purposively selected key informants (N = 45), representing the main actors in Mongolia's mixed health system. Results Private-for-profit hospitals are concentrated in urban areas, where their financial model is most viable. The result is the duplication of private and public inpatient services, both in terms of their geographical location and the range of services delivered. The combination of persistent inpatient-oriented care and perverse financial incentives that privilege admission over outpatient management, have created unnecessary health costs. The engagement of the private sector to improve population health outcomes is constrained by a series of issues of governance, regulation and financing and the failure of the state to manage the private sector as an integral part of its health system planning. Discussions/Conclusion For a mixed system like in Mongolia, a comprehensive policy and plan which defines the complementary role of private providers to optimize private public service mix is critical in the early stages of the private sector development. It further supports the importance of a system perspective that combines regulation and incentives in consistent policy, rather than an isolated approach to provide regulation.